Manajemen Tenaga Pendidik di Institut Agama Islam Negeri (IAIN) Takengon - Maulida (IAIN Takengon, 2021)
This study aims to describe the management of educators at IAIN Takengon. The discussion includes the planning process, program implementation and evaluation of educators at IAIN Takengon. The research method uses descriptive qualitative. Data collection techniques through observation, interviews and documentation. The results showed that the management of teaching staff at IAIN Takengon went well and smoothly. Planning for educators by analyzing the needs of educators through Job Analysis and Workload Analysis. Implementation of the teaching staff program through the selection of educators in accordance with the planned formation, placement according to the homebase, coaching and development of educators through seminars, training, workshops and improving academic qualifications. Evaluation of educators periodically every year, every semester and every three months. Assessment of the performance of educators through Employee Performance Targets, Lecturer Workload Reports, questionnaires and attendance.